Peran Pengelola Pesantren dalam Menyelesaikan Permasalahan di Pondok Pesantren Al-Manar Putri - Avivah Rahma Dini; Deti Novianti; Noer Hanifah Lestari; Anaas Tri Ridlo Dina Yuliana; Fadhlurrahman Fadhlurrahman (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
The manager of the Al-Manar Putri Islamic Boarding School, Pengasih, faces various problems faced by female students in the Islamic boarding school. These problems are considered as factors that hinder the development of the Islamic boarding school. Therefore, this research aims to find out what problems occur at the Al-Manar Putri Islamic Boarding School, Pengasih and how the Islamic boarding school managers overcome these problems. This research uses a qualitative method with a descriptive approach. The data collection techniques for this research use semi-structured interviews, non-participant observation and documentation and use analytical techniques in the form of data reduction, presentation and conclusions. This research revealed that at the Al-Manar Putri Islamic Boarding School, Pengasih, problems were found such as self harm, jealousy between friends, the existence of friendship circles and dating cases and the boarding school management had tried their best to resolve these problems by giving advice, pay more attention to the female students, take them to a psychologist, take them out, analyze and check the problem.